The Politics and Economics of Public Spending - Schultze, Charles L. (Washington DC : The Brookings Institution, 1968)
The book discusses the strength and weaknesses of both the analytical and the bargaining approach to program decisions, and suggests how the two can complement each other.
Includes index
osc 14/06/17
Loans
Keywords: Political economy